Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1126/science.288.5468.1019
|View full text |Cite
|
Sign up to set email alerts
|

Earliest Pleistocene Hominid Cranial Remains from Dmanisi, Republic of Georgia: Taxonomy, Geological Setting, and Age

Abstract: Archaeological excavations at the site of Dmanisi in the Republic of Georgia have uncovered two partial early Pleistocene hominid crania. The new fossils consist of a relatively complete cranium and a second relatively complete calvaria from the same site and stratigraphic unit that yielded a hominid mandible in 1991. In contrast with the uncertain taxonomic affinity of the mandible, the new fossils are comparable in size and morphology with Homo ergaster from Koobi Fora, Kenya. Paleontological, archaeological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
255
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 614 publications
(274 citation statements)
references
References 22 publications
4
255
0
5
Order By: Relevance
“…Although these specimens have in fact been referred to the taxon Homo ergaster, for geographical reasons they could conceivably be relevant to the origin of the Flores hominid. The four skulls from Dmanisi have a mean cranial capacity of only 664 cc (range, 600-775 cc) (Gabunia et al, 2000;Vekua et al, 2002;Rightmire et al, 2006). It has been suggested that the Flores hominid descended from such a small-brained population, but this proposal is also unconvincing.…”
Section: Cranial Capacitymentioning
confidence: 99%
“…Although these specimens have in fact been referred to the taxon Homo ergaster, for geographical reasons they could conceivably be relevant to the origin of the Flores hominid. The four skulls from Dmanisi have a mean cranial capacity of only 664 cc (range, 600-775 cc) (Gabunia et al, 2000;Vekua et al, 2002;Rightmire et al, 2006). It has been suggested that the Flores hominid descended from such a small-brained population, but this proposal is also unconvincing.…”
Section: Cranial Capacitymentioning
confidence: 99%
“…It extends the Northeast Asian fossil hominin record by ca. 500 ka as Gongwangling is now close in age to the earliest Eurasian hominin fossils, such as the 1.75 Ma specimens from Dmanisi, Georgia (Gabunia et al, 2000;Ferring et al, 2011), and Sangiran (ca 1.5e1.6 Ma), Indonesia (Larick et al, 2001). Gongwangling is thus now the second oldest site outside Africa with cranial evidence for H. erectus.…”
Section: Discussionmentioning
confidence: 86%
“…The cranium was identified as H. erectus, but considered as more primitive than those from Zhoukoudian near Beijing and Trinil in Java (Woo, 1965). Its cranial capacity (780 cm 3 ) is almost identical to that of specimen D2880 (775 cm 3 ) from Dmanisi, Georgia (Gabunia et al, 2000;Rightmire et al, 2006), and is smaller than those from younger Chinese Middle Pleistocene adult hominins (Anton, 2002). Wu and Poirier (1995) and Schwartz and Tattersall (2003) provide detailed summaries.…”
Section: The Gongwangling Craniummentioning
confidence: 83%
See 2 more Smart Citations